Karakteristik tanah ordo ultisol di perkebunan kelapa sawit PT. Perkebunan Nusantara I (Persero) Cot Girek Kabupaten Aceh Utara - Andalusia, Bunga; Zainabun, Zainabun; Arabia, Teti (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala)
Ultisols have morphological characteristics, physical and chemical soil. It is necessary to study the characteristics of Ultisol in PT. Perkebunan Nusantara I (Persero) Cot Girek North Aceh Regency. The methode used descriptive quantitative survey methods. The study states that the structure of the soil in the study area tend to belong to the group of angular blocky. Soil consistency ranged from slightly tacky to the plastic. The texture of the clay causes consistency becomes more closely at the upper horizon and not easily destroyed (plastic) on the bottom horizon. Relatively high value of bulk density (1.31 g cm3-1 to 1.48 g cm3-1), permeability is slow (0.25 cm hr-1 to 0.51 cm hr-1), so that the soil porosity is less good. Land in the study area react sour, the cation exchanged capacityÂ value is low to moderate (11 me 100g-1 to 37 me 100g-1). N-total classified as moderate to very low (0.05% to 0.30%), available P was low (0.73 ppm to 4.08 ppm), the contents of Al and H is high enough so that the low fertility rate.